Recent Cyber-Physical-System developments and their safety & security management risk factors - Lindhout, Paul; Reniers, Genserik (Journal of Progress in Safety & Security, 2025)
Introduction: Recent developments in a wide variety of cyber-physical system (CPS) designs have resulted in many safety and security concerns. These are caused by increasing complexity, connectivity to the outside world, and a variety of component types, all contributing to increased system vulnerability. Simultaneously, the use of digital models, big data analytics, remote computing, online services, and machine learning extends manufacturing systems far beyond their physical and visible boundaries. Focusing on industry and healthcare settings, this study explores the challenges faced by safety and security management originating from these developments. Method: The scoping review method was used to gather literature on safety and security concerns. These are grouped and linked to the CPS components. Subsequently, their impact is reviewed from the perspective of safety and security management systems. Results: The findings indicate that safety and security management become entangled, many new risks need to be considered, and the availability of online digital real-time system components and employee skills are critical factors. Some of the sensors and safety metrics software must now be classified as safety-critical because robots and people have started to share the same workspace. The rapid developments and many unresolved issues on design, ethics, data and software quality, external supervision, standards and guidance, legal frameworks, and online system components abroad urgently require attention. In the discussion, several recommendations are made regarding how safety and security management can address these challenges. Conclusions: While robots and people increasingly mingle on shop floors and in care situations, safety management is lagging behind current CPS developments. New critical safety aspects require the attention of safety and security management. Practical applications: These findings in safety and security management systems will contribute to avoiding harm to people and the environment in companies operating CPS. One sentence summary: This study presents a structured way to deal with safety management of Cyber-Physical-Systems.